Alexander Blok on the Émigré Press: A.F. Damanskaya vs A.S. Yashchenko - Anfisa D. Savina (Литературный факт)
The article examines Alexander Blok’s late note on the émigré press, written for the unpublished Literaturnaya Gazeta [Literary Gazette]. The context that influenced the creation of the note is reconstructed through the use of archival materials preserved in the A.M. Gorky Аrchive of the IWL RAS, specifically the protocols of editorial board meetings of the Vsemirnaya Literatura [World Literature] publishing house, where Blok was involved. The research establishes that the text was a distant response to a polemic that unfolded after H.G. Wells’ visit to Russia in the autumn of 1920 (publications by D.S. Merezhkovsky, I.S. Bunin, and other émigré authors on one side, and responses by N.S. Gumilyov and K. Chukovsky on the other). Furthermore, as the analysis of the protocols shows, Blok’s theses reflect his familiarity not only with the materials of the journal Russkaya Mysl [Russian Thought] published in Sofia (as noted in E.I. Zamyatin’s memoir essay) but also with the newspaper Narodnoye Delo [The People’s Cause] (Reval) and the journal Russkaya Kniga [The Russian Book] (Berlin). Thus, criticizing the émigré press, Blok names the translator and jour- nalist A.F. Damanskaya, whose publications in the Reval newspaper were discussed at meetings of the editorial board of Vsemirnaya Literatura. At the same time, noting a positive shift in the attitude of foreign Russian-language publications towards writers who remained in Russia, Blok refers to the critical-bibliographic journal published by A.S. Yashchenko. The article emphasizes that in his attempt to “build a bridge of understanding between émigré writers and those who remained,” Blok aligns himself with A.N. Tikhonov, despite his antipathy towards the latter.